Paramoera anivae a new species of Eusiridae Stebbing, 1888 (Crustacea: Amphipoda: Gammaridea) from the Okhotsk Sea - Labay, Vjacheslav S. (Zootaxa, 2012)
A new amphipod species, Paramoera anivae sp. nov., from upper littoral of Aniva Bay of Sakhalin Island (Russian FarEast) is described. The new species belong to the species group of Paramoera without spines or teeth dorsally, inner plateof maxilla 1 with 5 plumose strong setae, inner plate of maxilla 2 with oblique row of 3–4 plumose long setae on inner margin.